2020
DOI: 10.1002/jbm4.10370
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast–Osteoclast Coculture Amplifies Inhibitory Effects of FG‐4592 on Human Osteoclastogenesis and Reduces Bone Resorption

Abstract: The link between bone and blood vessels is regulated by hypoxia and the hypoxia-inducible transcription factor, HIF, which drives both osteogenesis and angiogenesis. The recent clinical approval of PHD enzyme inhibitors, which stabilize HIF protein, introduces the potential for a new clinical strategy to treat osteolytic conditions such as osteoporosis, osteonecrosis, and skeletal fracture and nonunion. However, bone-resorbing osteoclasts also play a central role in bone remodeling and pathological osteolysis,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…This differentiation was confirmed by changes in cellular morphology (significant increase in multinucleation, ruffled border, and cell diameter) and by increased expression of TRAP, a typical OC marker [55] . Unlike other different hydrogel systems for culturing OC (such as gellan gum, alginate or hyaluronic acid hydrogels [63] , [64] , [65] ), our system resembles the typical OC-bone interface. In fact, despite its limitations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This differentiation was confirmed by changes in cellular morphology (significant increase in multinucleation, ruffled border, and cell diameter) and by increased expression of TRAP, a typical OC marker [55] . Unlike other different hydrogel systems for culturing OC (such as gellan gum, alginate or hyaluronic acid hydrogels [63] , [64] , [65] ), our system resembles the typical OC-bone interface. In fact, despite its limitations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that the effect of HIF-2α siRNA was different when osteoclastogenesis was performed in 3D, rather than 2D, culture; resulting in an increase, rather than a reduction, in the number of osteoclasts formed. It is not uncommon for cells cultured in 3D to exhibit altered sensitivity to cytokines, inhibitors or drugs 33,38,39 or a stronger differentiation response 38,40 , but we can find no other reports of a reversal in the direction of effect of a stimulus due to 3D culture. It is possible www.nature.com/scientificreports/ that this relates to the microenvironment-and tissue-specific nature of the regulation and phenotypic effects of HIF-2α 4,5 and is an area of considerable interest for future study.…”
Section: Discussionmentioning
confidence: 62%
“…3 b). We recently reported that osteoclastogenesis can be differentially affected in 3D versus 2D culture 33 . In contrast to standard culture conditions, HIF-2α siRNA caused a moderate increase in osteoclast formation when cells were cultured in 3D collagen gels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potent HIF-α stabilizer, roxadustat was found to promote fracture healing by stimulating the proliferation and migration of bone marrow mesenchymal stem cells, in which activation of the HIF-1α pathway was shown to be critical [ 15 ]. Moreover, roxadustat inhibited osteoclast differentiation and reduced bone resorption in vitro [ 16 ]. However, the effects of roxadustat on osteoblast differentiation and bone remodeling remain unknown.…”
Section: Introductionmentioning
confidence: 99%